2018
DOI: 10.1530/erc-17-0415
|View full text |Cite
|
Sign up to set email alerts
|

Notch pathway inhibition targets chemoresistant insulinoma cancer stem cells

Abstract: Insulinomas (INS) are the most common neuroendocrine pancreatic tumours in humans and dogs. The long-term prognosis for malignant INS is still poor due to a low success rate of the current treatment modalities, particularly chemotherapy. A better understanding of the molecular processes underlying the development and progression of INS is required to develop novel targeted therapies. Cancer stem cells (CSCs) are thought to be critical for the engraftment and chemoresistance of many tumours, including INS. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 62 publications
1
21
0
4
Order By: Relevance
“…Unsupervised clustering of these DEGs showed that normal pancreatic tissues clustered with primary INS lesions from patients bearing early stage INS (TNM stage I), and clustered separately from primary INS lesions from patients bearing advanced stage disease (TNM stage II–IV). When comparing primary INS with INS-metastatic lymph nodes, only 164 DEG were identified, suggesting less transcriptomic variances between these tissues 21 . Unsupervised clustering showed that primary INS from patients with high-grade INS (Grade 2) clustered together with the INS-metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unsupervised clustering of these DEGs showed that normal pancreatic tissues clustered with primary INS lesions from patients bearing early stage INS (TNM stage I), and clustered separately from primary INS lesions from patients bearing advanced stage disease (TNM stage II–IV). When comparing primary INS with INS-metastatic lymph nodes, only 164 DEG were identified, suggesting less transcriptomic variances between these tissues 21 . Unsupervised clustering showed that primary INS from patients with high-grade INS (Grade 2) clustered together with the INS-metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in gene expression of pairwise comparisons were organised as follows: (i) normal pancreas against primary INS; (ii) primary INS against INS-metastatic lymph nodes; (iii) normal lymph nodes against INS-metastatic lymph nodes. The normalised gene counts for differentially expressed genes were analysed for hierarchical clustering analysis with the R package “heatmap2” 21 , 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the γ-secretase inhibitor RO4929097 can significantly inhibit Notch target genes Hes1 and Hey1, and it is in a phase II clinical setting to treat breast cancer, ovarian cancer, and renal cell carcinoma [67]. The combination of RO4929097 and 5-FU can decrease the proportion of the CSC subgroup with insulinomas (INS) [68]. DAPT (GSI-IX) is a new type of Notch1 inhibitor that was initially used to treat Alzheimer's disease, and increasing number of studies have shown that it can inhibit CSCs [69].…”
Section: Notch Signaling Pathway Inhibitorsmentioning
confidence: 99%
“…Likewise, Notch signaling has now long been found to be altered and pathophysiologically involved in pancreatic carcinogenesis. Various approaches to pharmacologically target oncogenic Notch signaling in different cancers including pancreatic cancer have been developed, including the application of γ-secretase inhibitors and antagonists against Notch ligands [73,74,75], and some of these endeavors are still underway at various stages of preclinical as well as early clinical evaluation [76,77,78,79,80,81,82]. …”
Section: Novel Therapeutic Targetsmentioning
confidence: 99%